Impact of Maternal Endocrine Health on Foetal Development and Pregnancy Outcomes - Sundaram, Vickram Agaram; Chandrababu, Prasanth; Sowndharya Balamurugan, Bhavani; Saravanan, Bharath; Chinnakannu Marimuthu, Mathan Muthu; Thanigaivel, Sundaram; Anbalagan, Saravanan; Arora, Sonia; Chopra, Hitesh (Scripta Medica, 2025)
Maternal endocrine health is an essential predictor of favourable pregnancy outcomes, regulating both foetal development and maternal well-being. Pregnancy relates to significant hormonal changes that promote maternal-foetal connection and foetal growth. Maternal endocrine disturbances, whether caused by pre-existing illnesses or pregnancy-induced problems, can harm both the foetus and the mother. This review delves into the physiology and adaptations of the maternal endocrine system, concentrating on major organs such as the thyroid, pancreas, adrenal glands and placenta. The pathogenesis of gestational diabetes and thyroid dysfunctions and their effects on mother and foetal health. During pregnancy, it impairs foetal neurodevelopment, growth and congenital malformations, often caused by hormonal imbalances and disruptors. Polycystic ovary syndrome (PCOS), though not a gestational disorder, is a major preconception risk factor for infertility, gestational diabetes and adverse perinatal outcomes. These endocrine perturbations collectively contribute to an elevated risk of obstetric complications, including preterm birth, stillbirth and neonatal morbidity. These endocrine perturbations lead to an elevated risk of obstetric complications, including preterm birth, stillbirth and neonatal morbidity. Furthermore, environmental and epigenetic factors are evaluated in mother-foetus health due to their potential transgenerational consequences. Future research directions include combining personalized medicine, omics technologies and artificial intelligence to improve maternal-foetal outcomes. Improved diagnosis accuracy, treatment efficacy and preventative care will also contribute to the achievement of numerous Sustainable Development Goals, such as improving health and well-being, eliminating health-care disparities and supporting maternal-foetal health innovation. This study highlights the critical need to increase global efforts to promote maternal-foetal endocrine research and treatment.